Effects of Attribute Affirmation and Achievement Goals on High School Students' Motivation - Liu, Cheng-Hong; Huang, Po-Sheng; Yin, Xian-Rui; Chiu, Fa-Chung (Frontiers in Psychology, 2021)
Researchers have suggested that receiving attribute affirmation (AA) may increase the motivation of students to confront a challenge. However, we posited that to determine whether AA increases the motivation of students to confront a challenging task, we must consider dispositional achievement goals of the students. The participants were 171 junior-high-school students, randomly assigned to an AA or no affirmation condition. The results showed that AA enhanced the tendency to confront a challenging task for students who endorsed low mastery-approach goals (MAGs) and low performance-approach goals (PAGs) simultaneously (b = 0.5, p = 0.015). The effect was mainly mediated by the increasing state performance-approach goals (SPAGs) in confronting the task (indirect effect = 0.21, 95% CI = 0.04–0.49); however, being attribute-affirmed decreased the tendency to confront the challenging task for students adopting a dominant PAG orientation (b = −0.76, p = 0.049). In addition, for students adopting a dominant MAG orientation or adopting high MAGs and high PAGs simultaneously, no difference was noted in the tendency to confront the task between participants in the control and attribute-affirmed conditions.